Penggunaan Model Discovery Learning dalam Pengenalan Lingkungan Persekolahan di SMAN 6 Pandeglang - Sabrina Oktaviantri Sagita Putri; Ayu Harisa; Siti Nurasiah; Najwa Qonita Mumtazah; Neng Melisa; Wilda Alif Roisatun Nisa; Rifka Reviliana; Nursabrina Laila Warohmah; Siti Khairunnisa Hamidah; Wely Yuliati; Desi Yuningsih; Wahyuni; Retnita Anggraeni; Ahmad Supena (CV.ITTC INDONESIA, 2024)
This study aims to analyze the effectiveness of Discovery Learning model in the Introduction of School Environment (PLP) activities at SMAN 6 Pandeglang in Science and Technology subjects. The approach used is mix-method with descriptive method through observation, development of teaching tools, teaching practice, and data analysis of learning outcomes. Quantitative data were analyzed using SPSS with normality test and t-test to determine the suitability of the model at various grade levels. The results show that some classes require diverse learning models according to student characteristics, while other classes can use similar models with optimal results. These findings support the implementation of differentiation-based learning in Merdeka Curriculum, which emphasizes flexibility and adaptation of teaching tools. This research confirms the importance of continuous evaluation and the implementation of appropriate learning strategies to improve the effectiveness of classroom learning.